Operative treatment of trochanteric fractures with dynamic hip screw--is perioperative blood transfusion needed? - Chua, Y.P.; Kwan, Mun Keong; Saw, A. (Malaysian Medical Association, 2005)
The need for perioperative blood transfusion in elderly patients with trochanteric fracture scheduled for elective dynamic hip screw fixation has recently been questioned following reports on the association between allogeneic blood transfusion and post-operative infections. This retrospective study was undertaken to assess the amount of per operative blood loss and transfusion requirement in relation to pre-operative haemoglobin level in 198 patients with trochanteric fractures. The average per operative blood loss was 409 ml and it correlated well with the duration of the operation. More than half of the patients (52.5) required blood transfusion and nearly three-quarters were anaemic prior to the surgery. Proactive pre-operative measures to optimize the patient's haemoglobin level and intra-operative minimization of blood loss are essential steps to obviate the need for perioperative allogeneic blood transfusion.